Tuning Single‐atom Pt1−CeO2 Catalyst for Efficient CO and C3H6 Oxidation: Size Effect of Ceria on Pt Structural Evolution. Issue 12 (2nd October 2020) - Tan, Wei; Alsenani, Hatim; Xie, Shaohua; Cai, Yandi; Xu, Peng; Liu, Annai; Ji, Jiawei; Gao, Fei; Dong, Lin; Chukwu, Ewa; Yang, Ming; Liu, Fudong
Abstract: To reveal the effect of ceria particle size on dispersion and structure of supported Pt catalysts during preparation, activation, and reaction testing, a unique CeO2 /Al2 O3 support (CA−c) with smaller CeO2 particle size and more surface defects was prepared using a colloidal CeO2 precursor, comparing with a conventional CeO2 /Al2 O3 support (CA−n) using cerium nitrate as precursor. More atomically dispersed Pt and abundant Pt−O−Ce structures were observed in the Pt/CA−c catalyst than in the Pt/CA−n catalyst. Both parent catalysts received significant enhancement on their catalytic CO oxidation activities if activated by 10% hydrogen at 400 °C before reaction. Between the two representative catalysts, the extent of activity enhancement upon activation was more pronounced for Pt/CA−c. We found that smaller Pt clusters with more active ionic Pt sites were generated on the activated Pt/CA−c catalyst, while agglomerated larger Pt particles with more metallic sites were formed on the activated Pt/CA−n. The facile formation of Ce 3+ was also indicative of more active metal‐support interfaces in the activated Pt/CA−c catalyst. These results highlight the importance of regulating ceria support particles to enable a controlled anchoring and subsequent activation of Pt single atoms for low‐temperature CO oxidation reaction. Abstract : Highly dispersed Pt single atoms were created on a novel CeO2 /Al2 O3 support (CA−c) with small CeO2 particle size. After activation treatment, excellent catalytic oxidation performance was achieved on Pt/CA−c−ACT, resulting from the smaller Pt clusters with more active ionic Pt sites at the interface of Pt−CeO x .